Strategi Dinas Kelautan, Perikanan Dan Ketahanan Pangan Dalam Peningkatan Ekonomi Kelompok Pengolah Dan Pemasar (Poklahsar) Di Kabupaten Pangandaran - Priyambada Wira Adni Herlambang (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research was started because there was a problem where the economic existence of the people who were members of the Fish Processing and Marketing Group (Poklahsar) in Pangandaran Regency was still not optimal. Their income is still fluctuating. There are many obstacles, especially raw materials and nature, which greatly affect the process of implementing the processing and marketing of these fish, considering that not all fish can be processed and marketed, only certain fish can be processed and marketed, and even that is constrained by the season. Thus, the purpose of this study is to determine the strategy of the Department of Maritime Affairs, Fisheries and Food Security in improving the economics of the Processing and Marketing Group (Poklahsar) in Pangandaran Regency, the obstacles and efforts it has made. The method used is descriptive qualitative. The results of the study concluded that the Department of Marine Affairs, Fisheries and Food Security implemented the main generic, main and functional strategies in improving the economics of the Processing and Marketing Group (Poklahsar) in Pangandaran Regency. The obstacles faced by the Office of Maritime Affairs, Fisheries and Food Security in implementing strategies to improve the economics of the Processing and Marketing Group (Poklahsar) in Pangandaran Regency are human resources, raw materials, funds and prices. Efforts made by the Office of Maritime Affairs, Fisheries and Food Security to overcome obstacles in implementing strategies for improving the economy of the Processing and Marketing Group (Poklahsar) in Pangandaran Regency are conducting training and developing HR competencies, providing injections of funds and assistance with processing infrastructure facilities to Poklahsar, and set prices. While the raw materials have not yet found its efforts.